(untitled) (Tintas: Quaderni di Letterature iberiche e iberoamericane, 2021)
I am considering in this work if Salvador Jacinto Polo de Medina was in fact the author of the invective in the form of a dream called Universidad de amor y escuelas del interés, which was published first under the pseudonym of Maestro (or even Bachelor) Antolínez de Piedrabuena and some later in Paris, in 1661 with the initials F.P. I will approach here not only its paratexts but also the translation into French. I have also found an unknown edition of Universidad de amor y escuelas del interés. Verdades soñadas o sueños verdadero. Al pedir de las mujeres, printed by Luis Veros in Murcia in 1664, which probably was the first one. Similar works like El hijo de Málaga, El lazareto de Milán, Noches de convalecencia and, the not so well known, Grandezas del color pardo. Asunto propuesto en competencia de colores por la ilustre y docta Academia de Madrid, were also attributed to the same author, who had to hide himself also under the pseudonym of Fabio Vigilio Cordato.